Jesus In Abrahamic Traditions: A Comparative Study - Mohamad Hasmimie Bin Mohd Yusof
Islam, Christianity and Judaism are the three religions called the Religion or Abrahamic Traditions (Abrahamic Traditions) which are attributed to the Prophet Abraham. Every prophet and apostle including Isa a.s was sent to bring the same teachings. However, there are interpretations of the nature and teachings brought by Isa a.s. As a result of that there was a debate in determining the teachings and views on the personality of Isa a.s. Therefore, this study aims to find the similarities and differences of views on Isa a.s in creating harmony as well as mutual respect for their respective interpretations. This study adapts qualitative research to collect and analyze data. This study concludes that Islam, Christianity and Judaism have different perceptions and beliefs on the personality of Isa a.s. Even so, all three religions still respect the morals exhibited by Isa a.s. Their views give an understanding to the followers of their respective religions to respect each other and live in harmony.